Dampak Perubahan Work From Home Terhadap Motivasi Kinerja Karyawan Dimasa Pandemi Covid-19 - Silvi Tri Wardani; Nuri Aslami (Jurnal Manajemen Akuntansi (JUMSI), 2022)
The world, including Indonesia, is being hit by Corona Virus Disease (Covid-19). Even though direct labor is often carried out in schools, the effects of Corona Virus Disease (Covid-19) are felt in the workplace. Work has to be done remotely or online during the coronavirus epidemic, which is often known as "work from home". In accordance with the Indonesian state plan, this policy was implemented to assist the government in reducing the spread of the corona disease. President Jokowi stated that this approach needs to work especially for those who study, work and worship at home. (prayer at home). Online information and communication technology is used to carry out the process of working from home (from home) (ICT). The application of the work from home system utilizes the idea of online work carried out under the management of the organization. Through online communication tools including WhatsApp, Telegram, Zoom, Meet Google, and company websites, employees perform work-related tasks. The purpose of this study was to evaluate the effect of allowing employees to work from home during the COVID-19 epidemic on employee performance motivation. It is very important for employees to be able to work from home during the COVID-19 epidemic. The effectiveness of the company's personnel in carrying out its operations affects the success of the company. Due to the rapid development of information technology in the modern era, including Whatsapp, Telegram, Zoom, and others, the work process went smoothly.